The Psychodidae (Diptera) of Fernando de Noronha, Brazil, with a records overview of volcanic islands fauna - Vieira, Gabriel Santos; Bravo, Freddy; Limeira-De-Oliveira, Francisco; Rafael, José Albertino (Zootaxa, 2024)
The family Psychodidae (Diptera) is recorded for the oceanic archipelago of Fernando de Noronha, represented by two genera and three species: Clogmia albipunctata Williston, Psychoda buxoides Quate, P. savaiiensis Edwards, as well as an undetermined species belonging to the tribe Pericomaini. The fauna of Psychodidae in Fernando de Noronha is remarkably inferior to the Brazilian continental fauna, including species known as cosmopolitan due to the introduction into the most varied environments by human action. An identification key for the Psychodidae of Fernando de Noronha is given, and an overview of the records of Psychodidae for volcanic islands worldwide is also provided.